INVENTORY OF ECTOPARASITES IN AFRICAN CATFISH (Clarias gariepinus) AT AQUACULTURE SITES IN SUNGAI RAYA DISTRICT, KUBU RAYA REGENCY - Deddy Widiyantoro; Eko Dewantoro; Eko Prasetio (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
The african catfish (Clarias gariepinus) is one of the freshwater aquaculture species susceptible to ectoparasite infestations. This study aimed to identify the types of ectoparasites and determine the infestation levels in african catfish farmed in Sungai Raya Subdistrict, Kubu Raya Regency. The study was conducted from February to March 2026 using a survey method with purposive random sampling. A total of 95 catfish from five aquaculture sites were examined for mucus, fins, and gills using wet mount preparation and microscopic observation. Data were analyzed descriptively by calculating prevalence, intensity, and dominance. The results showed that African catfish were infected by three types of ectoparasites Dactylogyrus sp., Gyrodactylus sp., and Trichodina sp. with a total of 209 parasite individuals. Dactylogyrus sp. was the most dominant ectoparasite, with prevalence values ranging from 26.32–36.84% and dominance values ranging from 36.17–64.52%. Ectoparasite intensity values ranged from 2.33–6.00 individuals per fish, indicating a low to moderate level of infestation. Water quality parameters during the study remained within the optimal range for catfish farming. The presence of ectoparasites is believed to be influenced by environmental conditions and farming management practices. The results of this study can serve as baseline information for monitoring fish health and controlling diseases in African catfish farming